Use of National Traditions in the Teaching of Pedagogical Sciences in the System of Professional Education - Abdullaevna, Maftuna Menglikulova (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, the role of national and universal values in the professional education system, the new worldview based on the harmony of national and universal values in our country, and the essence of the work being carried out on the formation of healthy thinking are highlighted.